Social Determinants of Health Related to the Prevalence of Anemia in Pregnant Women in UPT. Singkawang Tengah City Health Center II, Singkawang City - Asmariana, Yully (Devotion : Journal of Research and Community Service, 2025)
The maternal mortality rate (MMR) in Indonesia is still high, with postpartum bleeding and iron deficiency anemia as the main causes. Anemia in pregnant women is influenced by nutritional factors, diet, environment, and social determinants of health, so that it has the potential to increase the risk of morbidity and mortality in mothers and babies. This study aims to analyze the social determinants of health including employment, parity, body mass index (BMI), age, chronic energy deficiency conditions (KEK), and nutritional status on the prevalence of anemia in pregnant women in UPT. Singkawang Tengah Health Center II Singkawang City. The research design uses an analytical survey with a cross sectional approach in July–December 2025. The population is all pregnant women recorded in the Maternal and Child Health reporting book from January 2024 to May 2025. The sample was determined by purposive sampling based on inclusion criteria, so that 371 respondents were obtained. Data analysis was carried out univariate, bivariate with chi-square test, and multivariate with binary logistic regression. The results of the univariate analysis showed a prevalence of anemia of 39.6%. Bivariate analysis found a meaningful relationship between occupation (p=0.040), BMI (p=0.045), arm circumference (p=0.026), and nutritional status (p=0.008) with anemia, while parity (p=0.918) and age (p=0.098) were not significantly related. Multivariate analysis showed the arm circumference of the SEZ (p=0.039; OR=0.56; 95% CI: 0.32–0.97) and nutritional status at risk (p=0.011; OR=1.76; 95% CI: 1.14–2.72) as the dominant factor for anemia prevalence. This study emphasizes the importance of ANC screening, balanced nutrition interventions and monitoring of KEK status from the beginning of pregnancy to reduce the risk of anemia and support healthy mothers, safe childbirth and healthy babies.